Pengembangan Sistem Inventory Alat Tulis Kantor (ATK) Berbasis Web - Umar, Rusydi; Muntiari, Novita Ranti; E, Ermin; Bustomi, Iqbal; Tella, Fitriyani (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Developments in the technological era are increasingly developing and people's needs vary with the desire to accelerate a job in a systematic and more effective and efficient manner. The problems faced by PT. XYZ in supplies of office equipment are still poorly organized and there is no reporting on the use of office stationery (ATK) and inhibitors of employee productivity because there is no precise inventory information and delays in making reports. Facilitates the company in the process of inventory input Application of the method in this research is to use the classic life cycle (CLC) method, known as the process design, which is carried out sequentially, with the research stages beginning with analysis, design, coding and testing.From the several stages that have been carried out in this researcher can produce reports stock of goods and office stationery information updated to users or visitors.